PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO YOUTUBE TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SDN 25 PULAU PUNJUNG - Suci Dwiva Azidha; Dodi Widia Nanda; Estuhono (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is motivated by the low learning outcomes of students due to the use of conventional learning methods that are teacher-centered and the lack of varied learning media. This condition causes students to become passive and less enthusiastic in the learning process. The purpose of this study is to determine the effect of the Problem Based Learning (PBL) model assisted by YouTube videos on the science (IPAS) learning outcomes of fifth-grade students at SDN 25 Pulau Punjung. This research uses an experimental method with a quasi-experimental approach and a Nonequivalent Control Group Design. The population in this study includes fifth-grade students at SDN 25 Pulau Punjung and class VA at SDN 10 Pulau Punjung. The sample consists of two classes: the experimental class using the PBL model assisted by YouTube videos, and the control class using the lecture method. The research instrument was a multiple-choice test administered as a pretest and posttest. The results of the hypothesis test showed a significance value of 0.000 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. Therefore, it can be concluded that there is a significant effect of using the Problem Based Learning (PBL) model assisted by YouTube videos on the IPAS learning outcomes of fifth-grade students at SDN 25 Pulau Punjung.